A top-down methodology for ultrafast tuning of nanosized zeolites1. Issue 63 (14th August 2015) - Liu, Zhendong; Nomura, Naoki; Nishioka, Daisuke; Hotta, Yuusuke; Matsuo, Takeshi; Oshima, Kazunori; Yanaba, Yutaka; Yoshikawa, Takeshi; Ohara, Koji; Kohara, Shinji; Takewaki, Takahiko; Okubo, Tatsuya; et al.
<x xml:space="preserve">Abstract</x> A top-down methodology to prepare nanosized zeolites with tunable size by combining post-synthesis milling and fast recrystallization of several minutes is developed.